Bloqueio da via da fractalcina reduz a hiperalgesia e impede alterações morfológicas gliais - diferenças entre as dores orofaciais inflamatória e neuropática em ratos - Lisboa, Mario Roberto Pontes (2019)
Orofacial pain, either inflammatory or neuropathic, affect up to 90% of the general population. Recently, glial cells have gained an increasing focus in the process of pain development. The fractalkine (FKN) pathway is a mechanism of crosstalk between neurons and glial cells which seems to be related to painful states. This pathway involves the activation of the purinergic receptor P2X7, secretion of cathepsin S e production of cytokines through the phosphorylation of the p-38 mitogen-activated kinase proteins (p-38 MAPK). The aim of this study was to evaluate the effects of inhibitors of the FKN pathway in hyperalgesia/allodynia in inflammatory and neuropathic orofacial pain in rats, focusing on the morphological changes in microglia and satellite glial cells (SGCs) and the differences among the experimental models of zymosan-induced temporomandibular joint arthritis and infraorbital nerve constriction. Seventy male rats were submitted to either zymosan-induced arthritis of the temporomandibular joint or infraorbital nerve constriction, and treated with intrathecal infusion of a purinergic P2X7 antagonist (BBG), a cathepsin S inhibitor (LHVS) or a p-38 MAPK inhibitor (SB203580). Mechanical hyperalgesia was evaluated 4h and 6h after arthritis induction or 7 and 14 days following nerve ligation. The expression of the FKN receptor (CX3CR1), phosphorylated p-38 MAPK (phospho-p-38 MAPK), ionized calcium-binding adapter molecule-1 (Iba-1; microglial marker) and glutamine synthetase (SGCs marker) and the morphological changes in microglia and SGCs were evaluated by immunofluorescence and confocal microscopy. Both experimental models were capable of increasing the expression of CX3CR1 (p < 0.05), indicating that the FKN signaling might be important in the development of painful conditions in the orofacial complex. In both inflammatory and neuropathic models, untreated animals developed hyperalgesia and up-regulation of phospho-p-38 MAPK, which was prevented by all drugs (p < 0.05). However, the model of neuropathic pain induced a more outstanding increase in p-38 MAPK phosphorylation, when compared to the inflammatory model (p < 0.05). The number of microglial processes endpoints and total branch length were remarkably low in the untreated animals, but the overall immunolabeling of Iba-1 was only altered by neuropathic pain (p < 0.05). The mean area of SGCs per neuron was significantly altered only in the inflammatory model (p < 0.05) and not in the animals with neuropathic pain. All morphological alterations 11 were, at least partially, reverted by the pharmacological modulation of the FKN pathway (p < 0.05). In conclusion, the blockage of the FRK pathway could be a possible therapeutic strategy for inflammatory and neuropathic orofacial pain, reducing mechanical hyperalgesia by the impairment of the phosphorylation of p-38 MAPK and reverting morphological alterations in microglia and SGCs of the trigeminal complex